Butterworth band-pass filter for GPS application / Mohd Fadzli Malek Riduan - Malek Riduan, Mohd Fadzli (2010)
This thesis presents the design of a Butterworth microstrip parallel couple band-pass filter (BBPF) for GPS application. Butterworth approach was used in designing the filter and the simulation was carried out using CST simulation software. The filter is designed with the operating frequency range from 1559MHz to 1610MHz with the cut-off frequency 1575MHz with the consideration of 24MHz bandwidth It wil demonstrate the third order of the Butterworth elements. The specified pass band insertion loss must not exceed 3dB while the pass band return loss was to be more than 20dB. The filter were fabricated on RT/ Duroid 4350B having a relative permittivity of 3.48, and substrate thickness 1.542mm respectively. The filters characteristic were then measured using Rhodes & Schwarz ZVR-40 vector network analyzer. The simulation result show a good agreement.